Selection of coffee progênies for resistance to leaf rust andr favorable agronomic traits - Dias, Rafael Almeida; Ribeiro, Marcelo Resende; de Carvalho, Alex Mendonça [UNESP]; Botelho, Cesar Elias; Mendes, Antonio Nazareno Guimarães; Ferreira, André Dominghetti; Fernandes, Fernando Costa (Coffee Science, 2019)
The objective of this study was to select coffee progenies with better assessment that can result in coffee rust resistant cultivars and better agronomic characteristics than the traditional ones. The essay was performed at the EPAMIG experimental field in Patrocínio, state of Minas Gerais, Brazil. Twenty-five progenies in the F3 generation were studied. The experiment was set in a randomized complete block design with three replicates and ten plants per plot, arranged in rows at 3.5x0.7m. Productivity assessment, fruit production, in liters of “farm coffee” per plot, bean rating in a sieve (16 or above), and plant vigor were accessed in three different harvest seasons (2011/2012 harvest to 2014/2015 harvest), and coffee rust incidence and severity were then evaluated for 2016. The production profit estimation through the selection was also assessed, by the gain of direct selection for each characteristic, when compared to the rank addition. Progenies 13 (Icatu V. IAC 4040 x IAC 5002) and 3 (Icatu A. IAC 2944 x IAC 5002) were promising in generation advance, for being among the five most productive progenies. The selection gain reached by direct selection was superior than the gain of the total rank additions.
Seleção de progênies de cafeeiro visando características agronômicas favoráveis
Keywords: Breeding genetic gain; Coffea arabica; Hemileia vastatrix; Icatu derivatives